A Critical Examination of Pakistan-US Relations - ul Abiden Malik, zain; Min Xing, Huang (Dinasti Publisher, 2021)
Both countries worked together in a variety of areas, with the United States giving Pakistan with economic, social, and military assistance. Two of the most well-known treaties and pacts made between the two countries to develop and improve relations were CENTO and SEATO. Pakistan has always satisfied American wishes, whether it is the Afghan War or the War on Terror. Both conflicts had devastating implications for Pakistan, with the country losing both economic and human resources. As a result of drawing Pakistan into direct warfare, trust between the two countries has eroded. Pakistan is still suffering as a result of US wars and requires financial support to recover.